The contemporary superintendent : (r)evolutionary leadership in an era of reform - Mountford, Meredith; Wallace, Leigh (Research on the superintendency, 2019)
"How can contemporary school district administrators, specifically superintendents, contend with so many difficult, and almost impossible competing commitments? Building on the definitions of revolution, revolutionary, evolution, and evolutionary, the notion of (R)Evolutionary Leadership emerged while discussing the need for school district leaders to push back against the status quo while improving teacher and leadership practices, improving student learning outcomes, engaging with the community, and ensuring decision making processes that include check and balance systems that are just, fair, and equitable for all. The chapters in this book introduce superintendents or research on superintendents in which these tenants were practiced; both in their ability to enact radical change by 'overthrowing' the status quo--as well as evolutionary in their deliberate approach to viewing change as a process they can control over time. These leaders were willing to confront and defy practices and policies that do not support student well-being and achievement, yet also know how to leverage what is to attain their desired result and future. The chapters chosen for inclusion in this volume are those that offered a glimpse of these revolutionary tenants in practice"--